2015
DOI: 10.1111/een.12251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant diversity and structural complexity on parasitoid behaviour in a field experiment

Abstract: 1. In natural ecosystems, plants containing hosts for parasitoids are often embedded within heterogeneous plant communities. These plant communities surrounding host-infested plants may influence the host-finding ability of parasitoids.2. A release-recapture-approach was used to examine whether the diversity and structural complexity of the community surrounding a host-infested plant influences the aggregation behaviour of the leaf-miner parasitoid Dacnusa sibirica Telenga and naturally occurring local leaf-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Although the enemies' hypothesis has received some empirical support in grasslands and agro-ecosystems (Andow, 1991;Langellotto & Denno, 2004;Letourneau et al, 2011;Scherber et al, 2010), its validity for forest is still debated (Letourneau, Jedlicka, Bothwell, & Moreno, 2009;Muiruri et al, 2016;Riihimäki et al, 2004;Schuldt et al, 2011). In addition, it must be noticed that the use of dummy caterpillars underestimates the importance of top-down processes as it does not capture the effect of other natural enemies such as spiders or parasitoids which are known to, respectively, respond to structural and chemical complexity of their habitat (Kostenko et al, 2015;Langellotto & Denno, 2004).…”
Section: Predation Barely Changed With Oak Neighbor Identitymentioning
confidence: 99%
“…Although the enemies' hypothesis has received some empirical support in grasslands and agro-ecosystems (Andow, 1991;Langellotto & Denno, 2004;Letourneau et al, 2011;Scherber et al, 2010), its validity for forest is still debated (Letourneau, Jedlicka, Bothwell, & Moreno, 2009;Muiruri et al, 2016;Riihimäki et al, 2004;Schuldt et al, 2011). In addition, it must be noticed that the use of dummy caterpillars underestimates the importance of top-down processes as it does not capture the effect of other natural enemies such as spiders or parasitoids which are known to, respectively, respond to structural and chemical complexity of their habitat (Kostenko et al, 2015;Langellotto & Denno, 2004).…”
Section: Predation Barely Changed With Oak Neighbor Identitymentioning
confidence: 99%
“…Due largely to their small size, the bulk of parasitoid knowledge comes from laboratory studies, and although this weakness was identified over a decade ago (Casas et al, 2004), parasitoid behavioral studies in the field are still sparse (but not absent, for examples see Heimpel & Casas, 2008;Randlkofer et al, 2010;Kostenko et al, 2015). The scarcity of supportive field studies means that it should not be automatically assumed that results generated in laboratory are applicable at the field level.…”
Section: Opiine Learning: From Lab To Fieldmentioning
confidence: 99%
“…Nontarget plants, be they plants which can support host insects but are currently uninfested, or simply other plants in the local environment which are never associated with the host insect, can emit cues that are detected by the olfactory system of a parasitoid and negatively impact foraging by masking the signals from the target host (Gingras et al, 2002;Obermaier et al, 2008;Quicke, 2014). In applied systems this may lead to released biological control agents dispersing and establishing within nontarget hosts, or a decline in female parasitoid fitness because of the requirement for increased searching time (Barratt et al, 2010;Kostenko et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In tritrophic interactions between plants, herbivores and predators, foraging behaviour of herbivores and predators may be differentially affected by characteristics of these patches, such as food-plant identity, vegetation composition and patch size. In a metapopulation composed of patches of varying quality, apparency or vegetation composition, some patches may provide a refuge for herbivores, while others may be heavily exploited by their natural enemies (Van Nouhuys and Hanski 2002, van Nouhuys 2005, Kostenko et al 2015. Thus, variation in vegetation context may determine local strength and stability of tritrophic interactions (Abdala-Roberts et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Plant-host-parasitoid systems are ubiquitous and the context-dependency of the associated tritrophic interactions is relatively well studied (Cronin and Reeve 2005, Kostenko et al 2015, Forbes et al 2018. Host-parasitoid dynamics are expected to be tightly linked because parasitoids are strongly dependent on the abundance of their hosts at the patch scale (Hagen et al 2012).…”
Section: Introductionmentioning
confidence: 99%